Результати тестування гальмівного механізму автомобіля Ford Focus ІІІ - Бевз, О. В.; Алієв, Ш. Р.; Алієва, Г. Н.; Бевз, О. В.; Алиев, Ш. Р.; Алиева, Г. Н.; Bevz, O.; Aliyev, S.; Aliyeva, G. (ЦНТУ, 2019)
Стаття присвячена дослідженню пари тертя – «гальмівний диск – гальмівна колодка». На основі результатів проведених досліджень оцінювали ефективність роботи гальмівних колодок в різних умовах експлуатації. Дослідження проводилися на спеціальному стенді з використанням натурального гальмівного вузла автомобіля Ford Focus ІІІ. Статья посвящена исследованию пары трения - «тормозной диск - тормозная колодка». В данной работе приведены результаты исследований эффективности работы пары трения в лабораторных условиях. На основе результатов проведенных исследований работы пары трения с учетом разных условий работы после окончания всех исследований проводилась оценка абсолютного и удельного износа колодок. Исследования проводились на специальном стенде с использованием натурального тормозного узла автомобиля Ford Focus ІІІ. In hired the results of researches of efficiency of work in the laboratory terms of pair of friction are pointed - a «brake disk is a skid». On the basis of results of the conducted researches of work of pair of friction - a «brake disk is a skid» taking into account different terms works after completion of all researches an estimation was conducted absolute and specific wear of brake pads. At this stand, the performance of all the pads in various braking modes was directly verified The studies were conducted on a special stand using the natural brake assembly of the car Ford Focus III. In summary of these studies, we can conclude that all the pads showed a normal result, but in our opinion the best were the pads of the firm BOSCH (Germany) and ZIMMERMANN (Germany). However, each owner has the right to decide which pads he will install on his car Ford Focus IІI.
Исследование надежности тормозного механизма автомобиля Ford Focus ІІІ
The Study of the Reliability of the Brake Mechanism of the Car Ford Focus III
Keywords: гальмівні колодки; гальмівний диск; питоме спрацювання; температура; тормозные колодки; температура; тормозной диск; удельный износ; skids; temperature; brake disk; specific wear